Populist, negationist discourses of gender-based violence and sexual diversity in the post-pandemic: Analysis of the VOX case in Spain - Juárez Rodríguez, Javier; Piedrahita-Bustamante, Pedro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The article contextualizes the rise of authoritarian and anti-gender populism in the world and its relationship with the crisis of liberal democracy. A framework is proposed on the role of populist discourses that use "gender ideology" and then the case of the Spanish political party VOX is analyzed. The approach is mixed interdisciplinary with a methodological design that is anchored in the postulates of Critical Discourse Analysis. It is concluded that, in the midst of the crisis, conservative sectors achieved support using "gender ideology" by denying the rights of feminist movements and the LGBTQ+ population.